Aditif Pangan dalam Makanan Ultra-Proses: Mekanisme Stres Oksidatif dan Disfungsi Endotel - Dwi Widyawati; Ghea Farmaning Thias Putri; Zaenudin (PT Bukuloka Literasi Bangsa, 2026)
Introduction: Ultra-processed foods contain additives such as artificial sweeteners, emulsifiers, and preservatives that may contribute to oxidative stress and endothelial dysfunction, key mechanisms in cardiovascular disease. Objective: This review evaluated the role of food additives in inducing oxidative stress and endothelial dysfunction and summarized their potential cardiovascular mechanisms. Methods: A PRISMA-based literature search was conducted in PubMed, Scopus, ScienceDirect, SpringerLink, and Google Scholar for studies published between 2019 and 2026. Studies examining artificial sweeteners, emulsifiers, or preservatives in relation to oxidative stress, inflammation, endothelial dysfunction, or cardiovascular outcomes were included. Thirteen eligible studies were analyzed using narrative thematic synthesis. Results: Food additives may increase reactive oxygen species production, mitochondrial dysfunction, gut dysbiosis, chronic inflammation, lipid peroxidation, and impaired antioxidant defenses. Artificial sweeteners were associated with reduced nitric oxide bioavailability, emulsifiers with intestinal dysbiosis and inflammation, and preservatives with oxidative and inflammatory activation. These alterations may promote endothelial dysfunction and increase cardiovascular risk. Conclusion: Oxidative stress appears to be a central mechanism linking food additive exposure to endothelial dysfunction and adverse cardiovascular outcomes. However, direct human evidence remains limited, warranting further longitudinal and clinical studies. Keywords: endothelial dysfunction, food additives, oxidative stress, ultra-processed foods, vascular health